News Media Framing of Grassroots Innovations in Denmark, the Netherlands and Sweden. Issue 5 (4th July 2021) - Magnusson, Dick; Sperling, Karl; Veenman, Sietske; Oteman, Marieke
ABSTRACT: This paper explores how grassroots innovations are being framed in the news media in Denmark, the Netherlands and Sweden. By using framing analysis of newspaper items in the three countries, based on 30 cases, we identify that compared to literature on framing of renewable energy, the results show a prevalence of frames labeled as "social" as well as positive framing in the media when reporting about grassroots innovations. There are differences between the countries, as social frames are significantly more common in the Netherlands while innovation stands out in Denmark. We argue that this reflects the energy landscapes in the countries, as grades of centralization and to which extent the country has transformed the energy system impact on how the grassroots innovations are being reported. Aspects of energy democratization is reflected in the reporting's as emphasis is often on local connection and benefits for communities and individuals. We finally argue that there is need for more studies on framing on grassroots innovations.